Efficacy and safety of single-dose onabotulinumtoxinA in the treatment of symptoms of osteoarthritis of the knee: results of a placebo-controlled, double-blind study. Issue 10 (October 2018) - McAlindon, T.E.; Schmidt, U.; Bugarin, D.; Abrams, S.; Geib, T.; DeGryse, R.E.; Kim, K.; Schnitzer, T.J.
Summary: Objective: To evaluate intraarticular onabotulinumtoxinA 400 U and 200 U in reducing symptoms of knee osteoarthritis (OA) in patients with nociceptive pain. Design: A multicenter, double-blind, randomized, placebo-controlled study was conducted in adults with knee OA and a painDETECT questionnaire score of ≤12 (indicating nociceptive pain). Patients were randomized to receive intraarticular onabotulinumtoxinA 400 U or 200 U or placebo (saline) in the study knee on a 1:1:2 ratio and were followed-up for 24 weeks posttreatment. The primary efficacy measure was the daily average numeric rating scale pain score for the study knee over 7 days at week 8. Secondary efficacy measures included the Western Ontario and McMaster Universities Osteoarthritis Index pain and physical function scores, the patient global impression of change score and the 7-day average worst pain score. Results: Of the 176 enrolled patients, 158 completed the study. The daily average pain score was reduced by approximately two points for all treatments (week 8); the reduction was sustained throughout follow-up, with no significant between-group difference between onabotulinumtoxinA and placebo (both doses: 0.22 [95% confidence interval (CI): −0.33, 0.76]; 400 U: 0.42 [95% CI: −0.26, 1.10]; 200 U: −0.03 [95% CI: −0.70, 0.64]). Similar results were found for all secondary efficacy measures. Treatment-related adverse events occurred in 3.4% of the pooled onabotulinumtoxinA group and placebo group; none were serious. Conclusions: There were no significant differences between onabotulinumtoxinA and placebo in reducing average pain score at week 8 compared with baseline in patients with knee OA. No safety concerns were identified. ClinicalTrials.gov identifier: NCT02230956 .